Development of Rapid and Visual Nucleic Acid Detection Methods towards Four Serotypes of Human Adenovirus Species B Based on RPA-LF Test. (4th October 2021) - Qi, Yong; Li, Wei; Li, Xiaoling; Shen, Wanpeng; Zhang, Jinhai; Li, Jiameng; Lv, Ruichen; Lu, Nianhong; Zong, Liqiang; Zhuang, Susu; Gui, Qiyuan; Zhou, Dongming; et al.
Abstract : Objectives . Human adenoviruses (HAdV) are classified as 7 HAdV species, and some serotypes in species B like HAdV 3, HAdV 7, HAdV 21, and HAdV 55 caused severe symptoms, even fatalities. Patients may be misdiagnosed and inadequately treated without reliable and practical methods for HAdV serotyping. Developing rapid, sensitive, and specific diagnostic methods for HAdV is critical. Methods . Detection methods were established based on a recombinase polymerase amplification (RPA) assay and lateral flow (LF) test. Specific target sequence was screened, targeting which, primers and probes were designed, synthesized, and screened for establishing assay with high amplification efficiency. Primer or probe concentrations and amplification time were optimized. Detection limit, sensitivity, and specificity were evaluated. Results and Conclusions . Simple, sensitive, and specific RPA-LF methods for detection of four serotypes of HAdV together or separately were established, which had detection limits of 10 to 280 copies/reaction comparable to real-time PCR without recognizing other pathogens. The sensitivity and specificity were >92% and >98%, respectively, evaluated by limited clinical samples. The detection can be completed in 25 min without requirement of any instrument except a constant temperature equipment, showing superior detection performance and promising for a wide use in the field and resource-limited area.